A comparative study of the effect of alcoholic extract of chasteberry thistle and atorvastatin on carbon tetrachloride-induced hepatotoxicity in mice. - يوسف أسعد (Latakia University Journal -Biological Sciences Series, 2023)
The present study aimed to make a comparison between the therapeutic effect of each of the alcoholic extract of the leaves of the chasteberry plant and atorvastatin when the hepatotoxic effect of carbon tetrachloride in whitemousesby identifying some biochemical changes of the studied groups. The study was conducted on 20 mice in four equal groups. The mice of the experimental groups were successively injected as follows: the first (control) with physiological solution NACL at a concentration of (0.9%), the second with a single dose of carbon tetrachloride (ccl4) (1.25 ml/kg), and the third with the same previous dose of ccl4 and daily doses of alcoholic extract of the leaves of the thistle plant for 10 weeks (250 mg / kg of body weight), and the fourth intraperitoneal once only in a dose of ccl4 (1.25 ml / kg) with daily doses of atorvastatin (10 mg / kg of weight body) for 10 weeks. The results of the biochemical study showed a significant increase (p < 0.05) in the mean values ​​of (AST) in the rats of the second group compared to the control, and the results also showed a significant decrease (p < 0.05) in the AST values ​​in the mice of the third and fourth groups compared to the control group. Second, while there were some changes in the values ​​with regard to blood sugar values ​​among the studied experimental groups, these changes were mostly not significant (p>0.05).